2019
DOI: 10.1051/0004-6361/201935355
|View full text |Cite
|
Sign up to set email alerts
|

Identifying galaxy mergers in observations and simulations with deep learning

Abstract: Context. Mergers are an important aspect of galaxy formation and evolution. With large upcoming surveys, such as Euclid and LSST, accurate techniques that are fast and efficient are needed to identify galaxy mergers for further study. Aims. We aim to test whether deep learning techniques can be used to reproduce visual classification of observations, physical classification of simulations and highlight any differences between these two classifications. With one of the main difficulties of merger studies being … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 62 publications
(60 reference statements)
1
79
0
Order By: Relevance
“…Ackermann et al 2018;Walmsley et al 2019). Following the approaches adopted for quantitative morphologies by calibrating on hydrodynamical simulations, Pearson et al (2019) train a CNN on synthetic Sloan Digital Sky Survey (SDSS) images of galaxies from the EA-GLE simulation (Schaye et al 2015) and examine biases from redshift, star-formation rates, and apparent brightness on merger and non-merger classifications -though with poor classification performance (65.5% in a binary classification). Nonetheless, one of the key elements of their synthetic SDSS images is that they were inserted into a handful of SDSS survey fields in an attempt to match observational biases in real images (realistic skies, resolution, and crowding by nearby sources).…”
Section: Introductionmentioning
confidence: 99%
“…Ackermann et al 2018;Walmsley et al 2019). Following the approaches adopted for quantitative morphologies by calibrating on hydrodynamical simulations, Pearson et al (2019) train a CNN on synthetic Sloan Digital Sky Survey (SDSS) images of galaxies from the EA-GLE simulation (Schaye et al 2015) and examine biases from redshift, star-formation rates, and apparent brightness on merger and non-merger classifications -though with poor classification performance (65.5% in a binary classification). Nonetheless, one of the key elements of their synthetic SDSS images is that they were inserted into a handful of SDSS survey fields in an attempt to match observational biases in real images (realistic skies, resolution, and crowding by nearby sources).…”
Section: Introductionmentioning
confidence: 99%
“…All ages and times are in Gyr. 3.50, 4.00, 4.50, 5.00, 5.50, 6.00, 6.50, 7.00, 7.50, 8.00, 8.50, 9.00, 9.50, 10.00, 10.50, 11.00, 12.00, 13.00 Table 5.8: Terms used when describing neural network performance from Pearson et al (2019) Term Definition Positive (P) An object classified in the catalogues or identified by a network as a merger. Negative (N) An object classified in the catalogues or identified by a network as a non-merger.…”
Section: Discussionmentioning
confidence: 99%
“…For the SDSS data, we use the network trained on SDSS images from Pearson et al (2019). The merging and non-merging galaxies used to train this network were collected following .…”
Section: Sdss Data Releasementioning
confidence: 99%
See 2 more Smart Citations